Peran Brand Kolaborator Dalam Memperkuat Produk Kustom Interaktif - Studi Kasus Kolaborasi Uniqlo dengan Indomie, Tolak Angin dan Gojek. - Siswanto, Riky Azharyandi; Yunidar, Dandi (Visualita Jurnal Online Desain Komunikasi Visual, 2023)
This study discusses how brand collaborations can enhance personal relationship with customers through interactive custom product offerings. The focus of this analysis is the collaboration between Uniqlo, a Japanese retail clothing company, and three local Indonesian brands - Indomie, Tolak Angin, and Gojek. The findings of this research reveal that these collaborations not only produce unique custom products but also strengthen the relationship between brands and customers with interactive products, creating a more intimate and personal shopping experience. This study highlights the importance of the right partner selection for maximum results in collaborations, considering the relevance and value that each brand can offer. Therefore, this study examines what factors support the success of this collaboration from the perspective of the strength of the brands chosen by Uniqlo in this collaboration. Applying a phenomenological study approach, the conclusion drawn from this study affirms that inter-brand collaboration plays a crucial role in creating the interactivity of the series of product experiences offered.